Pertanian Perdesaan Lampung: Peluang dan Tantangan Lampung Rural Agriculture; Opportunities And Challenges F - Fitriani Fitriani (Journal of Food System & Agribusiness, 2017)
The numbers of Lampung residents with average monthly expenditure per capita below the poverty line are still quite large (14.86%). Most of the poor are in the district (76.26%) and are rural communities dependent on the agricultural sector for their livelihoods. Rural agricultural communities face complex problems including: the limitations of land access, capital, technology, markets, and institutions. This project, conducted in 2014, was a series of research collaboration of universities (PEKERTI) between State Polytechnic of LampungÂ  (Polinela) as Research Team Proposer (TPP) with University of Lampung (Unila) as Research Partner Team (TPM). Method of depth analysis about Lampung rural agriculture society condition during 10 years and cross tabulation were conducted based on Lampung Input Output Table 2010. The secondary data were obtained from Provincial BPS (Lampung Statistic Office) and some other related technical agencies. The results of the discussion showed that the portrait of Lampung agriculture is dominated by rural farming which faces very complex problems. The complexity of the problems within agricultural society is a resultant of the limitations faced by farmers in accessing capital, land, technology and institutional resources. This condition boils down to structural poverty. The key to the work of sustainable rural agricultural development policy is the occurrence of synergy in overcoming obstacles which include: local agro-climatic conditions, site-specific technologies, availability of biomass, economic incentives, product markets, information access, land tenure, institutional, extension, and political constraints.